Fertility in High-Income Countries: Trends, Patterns, Determinants, and Consequences - David E. Bloom; Michael Kuhn; Klaus Prettner (Institute of Labor Economics (IZA), 2023)
High-income countries have generally experienced falling fertility in recent decades. In most of these countries, the total fertility rate is now below the level that implies a stable population in the long run. This has led to concerns among economists, policymakers, and the wider public about the economic consequences of low fertility and population decline. In this contribution, we aim to i) describe the main determinants of low fertility in high-income countries, ii) assess its potential economic consequences, iii) discuss adjustment mechanisms for individuals and economies, iv) propose a simple economic framework to analyze the long-run economic impact of low fertility, and v) draw lessons for economic policymakers to react appropriately. While the economic challenges of low fertility are substantial, a thoughtful and consistent policy response can mitigate most of the adverse consequences.
Keywords: J11; J13; O11; 330; low fertility; below replacement fertility; depopulation; economic consequences of population decline; long-run economic growth; economic policies to address low fertility